Media Animasi Menggunakan Macromedia Flash Berbasis Pemahaman Konsep Pokok Bahasan Persegi dan Persegi Panjang - Andini, Dita; Supriadi, Nanang (Desimal: Jurnal Matematika, 2018)
This study aims to develop animation media using Macromedia flash based on the conceptual understanding of the subject of rectangle and rectangle. The research and development method used is 4D model proposed by Thiagarajan consisting of 4 stages, namely: (1) define; (2) design; (3) develop and (4) disseminate. Researchers use data collection techniques is a questionnaire in the form of Likert scale for the response of learners. The result of the research is the animation media using Macromedia flash based on the concept of the subject of rectangular and rectangle that is suitable for learning media. The feasibility of learning media obtained from the validation of material experts with an average score of 3.40 is categorized valid and validation of media experts with an average score of 3.32 are categorized as valid. Student response to learning media obtained in small group test is very interesting with an average score of 3.64. In the large group, test obtained criteria attractiveness is very interesting with an average score of 3.47.